2022
DOI: 10.3847/1538-4357/ac9128
|View full text |Cite
|
Sign up to set email alerts
|

Testing Relativistic Reflection Models with GRMHD Simulations of Accreting Black Holes

Abstract: X-ray reflection spectroscopy is currently one of the leading techniques for studying the inner part of accretion disks around black holes, measuring black hole spins, and even testing fundamental physics in strong gravitational fields. However, the accuracy of these measurements depends on the reflection models employed for the spectral analysis, which are sometimes questioned. In this work, we use a general relativistic magnetohydrodynamic code to generate a thin accretion disk in Kerr spacetime and ray-trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…For example, current models normally assume Keplerian and infinitesimally thin accretion disks. At least in the case of fast-rotating sources, such a simple model works quite well, without introducing appreciable systematic uncertainties in the final measurements, as was shown by theoretical studies with GRMHD simulations (Shashank et al 2022) as well by the analysis of specific sources with models admitting deviations from Keplerian motion and disks with finite thickness (Abdikamalov et al 2020;Tripathi et al 2020Tripathi et al , 2021bJiang et al 2022). However, such a simple model breaks down, and we can encounter unacceptably large systematic errors if we do not properly select the sources; for instance, if we use our reflection models to analyze sources with a mass-accretion rate close to their Eddington limit (Riaz et al 2020a(Riaz et al , 2020b.…”
Section: Introductionmentioning
confidence: 83%
“…For example, current models normally assume Keplerian and infinitesimally thin accretion disks. At least in the case of fast-rotating sources, such a simple model works quite well, without introducing appreciable systematic uncertainties in the final measurements, as was shown by theoretical studies with GRMHD simulations (Shashank et al 2022) as well by the analysis of specific sources with models admitting deviations from Keplerian motion and disks with finite thickness (Abdikamalov et al 2020;Tripathi et al 2020Tripathi et al , 2021bJiang et al 2022). However, such a simple model breaks down, and we can encounter unacceptably large systematic errors if we do not properly select the sources; for instance, if we use our reflection models to analyze sources with a mass-accretion rate close to their Eddington limit (Riaz et al 2020a(Riaz et al , 2020b.…”
Section: Introductionmentioning
confidence: 83%
“…Relativistic signatures in X-ray spectra are stronger if the reflection component is strong and mainly generated in the very strong gravity region as close as possible the black hole, which, in turn, requires that the inner edge of the accretion disk is as close as possible to the black hole event horizon and the corona is compact and as close as possible to the black hole. It is also crucial to select sources with geometrically thin and optically thick accretion disks: theoretical and observational studies have shown that the simple Novikov-Thorne model with an infinitesimally thin disk works well as long as the disk is geometrically thin [28,29], while we can easily obtain incorrect measurements of the properties of the system if the accretion disk of the source is not geometrically thin [30,31]. A detailed discussion on the selection of spectra suitable for precise tests of General Relativity and on the systematic uncertainties in current X-ray reflection spectroscopy measurements can be found in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is extremely important to select sources with thin accretion disks. If we do not do so, we can easily get very precise but not very accurate measurements, which cannot be used to test General Relativity [85][86][87]. The construction of reflection models suitable to analyze X-ray data of black holes with thick disks is more challenging,…”
Section: Pos(multif2023)016mentioning
confidence: 99%